Apakah Disiplin Kerja, Motivasi Kerja dan Beban Kerja Mempengaruhi Produktifitas Kerja? - Shandra Bahasoan (STIE AMKOP, 2021)
This study aims to: 1) examine the effect of work discipline on work productivity, 2) examine the effect of motivation on work productivity and 3) examine the effect of work motivation on work productivity. This study uses quantitative methods with data collection in this study using questionnaires that were distributed directly to respondents. The population of this research is the lecturers of STIE Nobel Indonesia as many as 50 people with a saturated sample technique so that the total sample is 50 people. Data analysis with multiple linear regression approach. The results of the study found that work discipline, work motivation and workload had a significant positive effect on work productivity. Keywords: Work Discipline; Work Motivation; Workload; Work Productivity.